THE ASSESSMENT OF PROSPECTIVE APPLICATION OF MODERN LOGGING TECHNOLOGIES AND MACHINERY, BASED ON THE TECHNIQUES OF CALCULATING OPERATING COSTS - Yakobchuk , Valentyna (Forestry, Forest, Paper and Woodworking Industry, 2011)
Successful development of Ukraine’s forest sector is intimately associated with the improvement of logging operations efficiency. The current logging technologies and machinery, however, cannot be taken as being satisfactory in the field. The world’s modern practice is ever increasing focus on the short-log method of logging which has a number of advantages. The proposed methodological approach to calculating operational costs when using promissing logging techniques and machinery in the short-log method, may find wide use under conditions of Ukrainian forest management units